Analisis Efektifitas Sistem Informasi Akuntansi Biaya Operasional Sebagai Bentuk Pengendalian Internal PT. Solusi Bangun Karya - Azra, Azzuhairi; Pratiwi, Yanna Eka; Lastiani, Siwidyah Desi (JFAS : Journal of Finance and Accounting Studies, 2024)
Control is an important element in supporting the performance and sustainability of the company, especially in managing operational costs related to daily activities. An effective accounting information system can help identify, record, classify, and track operational costs precisely and accurately. This study aims to analyze the effectiveness of the operational cost accounting information system as a form of internal control at PT. Bangun Karya solution. Data collection methods include documentation, interviews, and observation sheets. Research data were analyzed through the stages of triangulation, reduction, and presentation of data. This study found that the accounting information system used by PT. Bangun Karya Solution is not utilised effectively as a means of financial internal control. Cash distributions and receipts are not clearly separated, increasing the risk of errors and fraud